4(7v-2)-7=4(1+7v)

Simple and best practice solution for 4(7v-2)-7=4(1+7v) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(7v-2)-7=4(1+7v) equation:


Simplifying
4(7v + -2) + -7 = 4(1 + 7v)

Reorder the terms:
4(-2 + 7v) + -7 = 4(1 + 7v)
(-2 * 4 + 7v * 4) + -7 = 4(1 + 7v)
(-8 + 28v) + -7 = 4(1 + 7v)

Reorder the terms:
-8 + -7 + 28v = 4(1 + 7v)

Combine like terms: -8 + -7 = -15
-15 + 28v = 4(1 + 7v)
-15 + 28v = (1 * 4 + 7v * 4)
-15 + 28v = (4 + 28v)

Add '-28v' to each side of the equation.
-15 + 28v + -28v = 4 + 28v + -28v

Combine like terms: 28v + -28v = 0
-15 + 0 = 4 + 28v + -28v
-15 = 4 + 28v + -28v

Combine like terms: 28v + -28v = 0
-15 = 4 + 0
-15 = 4

Solving
-15 = 4

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 4k(3+k)=-(2k+3) | | -9(z+5)=0 | | -9(z+6)=0 | | x(x-3)-x(x+5)+6=-2 | | 1-7n-2n=-8 | | 7-a=15a-2a | | -16x^2+3x+1.3=0 | | (23+5x)=(14x-3) | | 3(n-8)=4(n+2) | | (2n+5)(2n+3)=0 | | R=5x+43 | | (4g+7)+(7g+2)= | | 23+5x=14x-3 | | 4(c-3)+5=2c+3 | | 6(m+1)=3m-3 | | -3(a+4)=6 | | -g+6+2g=4g+4 | | 6x+7=2x-13 | | 12-1.7x=4.15 | | (x+1)+2(x-3)-5=(x+2)-(x+3)+2 | | ln(5x+3)=4 | | 27-3(2x+3)=2(1-3x) | | 7-n-6=-13+6n | | 12x^2+9x-20=0 | | 5(2.6x+3.9)=5 | | cos(2x)-5cosx+3=o | | .5x+7=2x+14 | | 1-4=7 | | 18-8(x+2)=2(x-9) | | 3x+5=-6x+32 | | -2/5(5x-20y) | | 2x^2+8x+n=15+n |

Equations solver categories